Intrathecal Hematoma and Arachnoiditis Mimicking Bacterial Meningitis After an Epidural Blood Patch. Issue 3 (September 2018) - Roy-Gash, F.; Engrand, N.; Lecarpentier, E.; Bonneta, M.P.
Abstract : ( Int J Obstet Anesth 2017;32:77–78) Epidural blood patch (EBP) is the most effective method to treat postdural puncture headache and has a low rate of complications. However, severe complications such as cauda equina syndrome and seizures have rarely been reported. This case report describes a woman who underwent an EBP and later presented with symptoms concerning for meningitis, but was ultimately found to have arachnoiditis from an intrathecal hematoma.